A new point of view on the relationship between global solar irradiation and sunshine quantifiers. (March 2016) - Brabec, Marek; Badescu, Viorel; Dumitrescu, Alexandru; Paulescu, Marius
Highlights: Prior knowledge: the relationship between the clearness index and relative sunshine is non-linear. Several formalized non-linear statistical models are studied. The linear with boundary jumps model shows that the nonlinearity is only apparent. The nonlinearity is mainly due to the boundary behavior (for relative sunshine of 0 or 1). Abstract: The relationship between the clearness index and the time averaged sunshine number is studied over short time intervals such as one hour. Several non-linear statistical models have been used. Meteorological and radiometric data from various weather stations of Romania (South-Eastern Europe) are analyzed. Nonlinearity of the relationship is only apparent near the boundary for relative sunshine σ of 0 or 1 and manifests itself in clearness index jumps mainly at σ  = 0 rather than σ  = 1. The negative clearness index jump at σ  = 0 decreases while the slope of the relationship increases when the sunshine number is averaged over longer time periods.